Answer:
Part 1: V = (x + 2)(x)(3x)
Part 2: V = 3x³ + 6x²
Part 3: A = 2[x(x + 2) + 3x(x + 2) + 3x(x)]
Part 4: A = 14x² + 16x
Step-by-step explanation:
The box has
Width = x,
Length = x + 2
Height = 3x
Part 1:
Volume of the box is given by, V = Length × Width × Height
⇒ V = (x + 2)(x)(3x) ....... (1) (Answer)
Part 2:
Hencem we can write from the equation (1)
V = 3x²(x + 2) = 3x³ + 6x² (Answer)
Part 3:
Totall surface area of the box is given by
sa = 2(wl + hl + hw)
⇒ A = 2[x(x + 2) + 3x(x + 2) + 3x(x)] ........ (2) (Answer)
Part 4:
So, from equation (2) we get,
A = 2[x² + 2x + 3x² + 6x + 3x²]
⇒ A = 14x² + 16x (Answer)